THE EFFECT OF PROBIOTICS WITH DIFFERENT DOSAGES ON THE GROWTH OF VANAME SHRIMP (Litopenaeus vannamei) - Mahfud Akbar; Muhammad Junaidi; Fariq Azhar (Journal of Fish Health, 2021)
Research on the effect of probiotic dosing on the growth of vaname shrimp (Litopenaeus vannamei). This research was conducted for 45 days from 26 August to 14 October 2019 which took place at UD Kolbun Nanda Mumbul Sari Village, Bayan District, North Lombok Regency, West Nusa Tenggara (NTB). This study used the CRD method (completely randomized design) with 5 treatments and 3 replications. The container used in this study was a sterofome with p 82 x50x38 cm, so that the area of ​​the container used was 155,800 cm3 and the volume of water in the container was 50 liters. The containers used were 15 sterofom units with 5 treatments and 3 replications, where in treatment one (P1) used probiotics at a dose of 0.2 ml / l / week, treatment two (P2) used probiotics at a dose of 0.4 ml / l / week, treatment three (P3) used probiotics at a dose of 0.6 ml / l / week, treatment four (P4) used probiotics at a dose of 0.8 ml / l / week, and treatment five (P5) used probiotics at a dose of 1 ml / l / week. Parameters observed during the study included growth rate, survival rate (SR), and feed conversion ratio (FCR) of vanname shrimp. The results showed that the administration of probiotics with different doses did not have a significant effect on growth in absolute weight and growth in daily weight. However, it had a significantly different effect on the survival rate and feed conversion ratio.